Risk Allocation under Liquidity Constraints - Péter Csóka; P. Jean-Jacques Herings (Fondazione Eni Enrico Mattei (FEEM), 2014)
Risk allocation games are cooperative games that are used to attribute the risk of a financial entity to its divisions. In this paper, we extend the literature on risk allocation games by incorporating liquidity considerations. A liquidity policy specifies state-dependent liquidity requirements that a portfolio should obey. To comply with the liquidity policy, a financial entity may have to liquidate part of its assets, which is costly. The definition of a risk allocation game under liquidity constraints is not straight- forward, since the presence of a liquidity policy leads to externalities. We argue that the standard worst case approach should not be used here and present an alternative definition. We show that the resulting class of transferable utility games coincides with the class of totally balanced games. It follows from our results that also when taking liquidity considerations into account there is always a stable way to allocate risk.
Keywords: C71; G10; 330; Market Microstructure; Coherent Measures of Risk; Market Liquidity; Portfolio Performance Evaluation; Risk Capital Allocation; Totally Balanced Games